Belonging - Hatcher, Robin Lee. (Grand Rapids, Mich. : Zondervan, 2011)
Trying to forget her painful past, Felicia Kristoffersen seeks to make a brighter future for herself as a teacher in Frenchman's Bluff, Idaho.
Keywords: Women teachers -- Fiction; Idaho -- Fiction; Fiction; Love stories